Energy-efficient and cost-effective water desalination using membrane distillation with air-cooled dehumidifier bank - Atia Khalifa; Mohamed Kotb; Suhaib M. Alawad (Energy Conversion and Management: X)
This study investigates the performance of a vacuum-assisted sweeping gas membrane distillation (SGMD) module integrated with an air-cooled bubble column dehumidifier (BCD) bank for energy-efficient and cost-effective water desalination. The system’s performance was analyzed based on heat and mass balance equations under natural and forced air cooling modes (air speeds: 0–8 m/s) for the BCD bank, identifying optimal operating conditions through parametric analysis of the system’s productivity and energy efficiency indicators. Results show that forced air cooling of the BCD bank improves the system’s flux by 40–100 % compared to the natural cooling mode. In addition, the system achieved a low specific energy consumption (SEC) of 500 kWh/m3 and a high gained output ratio (GOR) of 2 with cooling air speeds of 6–8 m/s. Energy consumption decreases by 37 % with forced cooling, while economic analysis reveals a 43 % reduction in water unit product cost at an air speed of 8 m/s. Exergy analysis highlights that the SGMD module accounts for most exergy loss, approximately three times higher than the BCD bank, particularly at higher feed temperatures (e.g. 90 °C). These findings establish benchmarks and provide clear guidelines for optimizing and developing SGMD-BCD systems, enhancing energy efficiency, productivity, and cost-effectiveness in desalination.